A component-testing framework - Östberg, Patrik (2006)
Ericsson Microwave Systems AB (EMW) in Luleå uses component-based development for their Command and Control systems. The need for a better way of testing these software components led to this master thesis. The goal was to investigate whether there were any existing testing frameworks and/or testing techniques that could be used and if not, create a new framework. To fulfil the goals of this master thesis, requirements were set up which were approved by EMW and an investigation of techniques that could be used and of existing testing frameworks was conducted. The techniques investigated were testing techniques as well as techniques that could be used to build a framework. Some of these were data-driven testing, keyword-driven testing, mock objects, XML parsing, and the reflection package in Java. The investigation of existing frameworks evaluated and compared some of the frameworks available at the time of this master thesis with each other and with the requirements. None of the found frameworks could test the components out of the box. However, there were those that features could be added to, to make them work. The work of adding these features and testing the modified framework after modification was estimated to be as much or more than building a new framework, which led to the decision to create a new framework. This framework uses keyword-driven testing, mock objects, XML among other things to fulfil the requirements. Validerat; 20101217 (root)